(untitled) (Progressive Agriculture, 2017)
A field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to examine the influence of number seedlings hill-1, rate and time of nitrogen application on the growth parameters of late transplant Aman rice (cv. BR23). The study, laid out in a RCBD with three replications, was comprised of three levels of number of seedlings hill-1 viz. 2, 4 and 6 seedlings hill-1, three nitrogen rates viz. 0, 60 and 120 kg N ha-1 and three levels of time of nitrogen application viz. nitrogen application in two equal splits at 15 DAT and early tillering stage (ET); nitrogen application in three equal splits at 15 DAT, ET and panicle initiation stages (PI); and nitrogen application in four equal splits at 15 DAT, ET, PI and flowering stages (F). The highest plant height (101.04 cm) was found at 80 DAT from 6 seedlings hill-1. 120 kg N ha-1 nitrogen application produced the tallest (104.08 cm) plant and nitrogen application in two equal splits at 15 DAT and ET gave the highest plant height (99.44 cm) at 80 DAT. The maximum number of tillers hill-1 (19.45) at 60 DAT and the highest leaf area index (3.08) at 40 DAT were found in the interaction effect among 6 seedlings hill-1, 120 kg N ha-1 and three times of nitrogen application at 15 DAT, early tillering and panicle initiation stages. The highest shoot dry matter hill-1 (28 g) was obtained as the interaction effect among 6 seedlings hill-1, 120 kg N ha-1 and nitrogen application in four equal splits at 15 DAT, early tillering, panicle initiation and flowering stages. The grain yield, although statistically non-significant, was numerically highest in seedlings hill-1, 120 kg N ha-1 and nitrogen application in three equal splits at 15 DAT, early tillering and panicle initiation stages. Therefore, transplanting with 6 seedlings hill-1 and application of 120 kg N ha-1 in 3-4 equal splits could be a better management practice for ensuring proper growth of the late transplant Aman rice. Progressive Agriculture 28 (3): 174-183, 2017